Problems of Foreign Language Teaching for Adult Veterinary Medicine Specialists: Reasons and Their Solution - Podoliak, Mykhailo (Educational Challenges, 2024)
Learning a foreign language by adults is one of the most critical aspects of lifelong learning in Ukraine. Many adults have worked in certain spheres of the Ukrainian economy; they must improve their qualifications once in a certain period. This should include specialized subjects and learning a foreign language. However, the organization of this process requires much effort and the unique skills of a language teacher since teaching a foreign language to adults can be fairly challenging, facing many problems. The article aims to determine the main problems and their solution in teaching foreign languages to adults.Methodology. We focus more on learning a foreign language in continuous education, using the example of specialists in the veterinary field of Ukraine. To conduct research, we interviewed 14 people aged 45 and over and 18 people aged 35-40 who studied at the Stepan Gzhytskyi National University of Veterinary Medicine and Biotechnologies of Lviv. In addition, English classes were held with eight persons from among those interviewed. The survey was conducted as an interview, where participants were asked to answer presented questions.Results. After interviewing the respondents of our study and analyzing the learning process, we can single out the most common problems when adults learn English: psychological, phonetic, lexical, and grammatical. The research results have demonstrated that teaching a foreign language to adult specialists requires the teacher's deep linguistic and psychological knowledge. Considering the problems raised during teaching, two groups of issues are solved by frequent training, explaining materials, memorizing rules, and vocabulary.Conclusion is psychological problems require a creative approach from a teacher to solve them.
Keywords: language teaching; adult specialists; lifelong learning; problems of foreign language learning